Investigation into micro and nano scale optical metrology for shiny surfaces and difficult to access aircraft engine components - Haridas, Aswin (Nanyang Technological University, 2020)
Industrial production has always been driven by global competition and the need for efficient market adaptation. A strategic initiative termed as Industry 4.0 was recently introduced to cater to these demands, which increased the requirements for both the manufacturing and the metrology sectors. It is predicted that the futuristic aircraft engines would contain large components with microscale features and those having areas that are difficult to access or complex internal channels. While the former requires dedicated measurement systems that challenge the physical limitations of optics, the accessibility of the latter set of components poses additional challenges. Currently available technologies for surface roughness evaluation are limited by, (i) small working distance (WD), (ii) small field-of-view (FOV), (iii) low measurement resolutions and (iv) inability to access complex internal channels. Therefore, techniques addressing the aforementioned limitations must be developed to ensure reliable quality control. In this context, the first objective of this research is to develop non-destructive optical techniques and image processing tools to measure the surface roughness parameters of large structures with micro-scale features (0.2 μm < average surface roughness, Ra < 0.6 μm). The thesis focuses on conceptualizing and developing speckle-based techniques for evaluating surface roughness parameters. An automated optical system based on the spectral correlation of laser speckle images was developed to address the requirements. The proposed configuration is capable of acquiring and processing data at high speeds (~ 1/15th the time taken for conventional measurement systems) and is therefore envisaged for reducing the processing time in large scale manufacturing. The measurement range of the developed system was determined to be 0.2 μm < Ra < 0.6 μm. The measurement results obtained from aerospace component surfaces as large as 450 mm × 210 mm were validated using a BRUKER CONTOUR GT 3D optical microscope. Two microscope configurations, namely, structured illumination Bessel beam microscope (SIBM) and structured illumination embedded speckle microscope are proposed for data-rich evaluation of surface roughness parameters. The SIBM configuration encompasses the imaging resolution enhancements offered by structured illumination microscopy (SIM) and a Bessel beam microscope (BBM). ZEMAX® simulations and experimental studies confirm sub diffraction resolution at long WD. Using a long WD objective lens (50X; 0.55 NA), the lateral resolution of the proposed SIBM was observed to be 505 ± 5 nm. On the other hand, structured embedded speckle illumination microscope enhances the imaging resolution by embedding static and dynamic speckle patterns within the conventional illumination patterns used in SIM. Using a long WD objective lens (50X; 0.55 NA), the lateral resolution of the microscope was observed to be 310 ± 5 nm. The mean square error (MSE) and signal-to-noise ratio (SNR) is calculated to determine the imaging quality, which was found to be improved by ~ 35%. Furthermore, using a long WD objective lens (20X, 0.4 NA, 19 mm WD), the optical sectioning ability (FWHM of the normalized intensity) was observed to be 3 μm (FWHM of the normalized intensity for a confocal microscope is 1 μm). The second major objective of this thesis is to miniaturize the developed measurement systems to measure the surface roughness parameters of components that are difficult to access or contain complex internal channels (5 μm < Ra < 20 μm). The optical systems based on speckle correlation and speckle imaging were miniaturized using two optical fiber probes, each having a diameter of ~ 2 mm and ~ 0.7 mm, respectively. In addition, novel image processing techniques were developed for the extraction of various surface roughness parameters from the captured images. It is envisaged that the developed systems can enable a paradigm shift, not only in the aerospace industry but in other industrial areas such as automotive, marine, and medical. Especially for the aerospace industry, the developed techniques can be used for line side inspection that can improve the manufacturing product quality and overall manufacturing cycle time.